KUALITAS BIOPELET DARI LIMBAH BATANG KELAPA SAWIT PADA BERBAGAI UKURAN SERBUK DAN JENIS PEREKAT - fian, Zul; Diba, Farah; Setyawati, Dina; haida, Nur; Roslinda, Emi (JURNAL HUTAN LESTARI, 2015)
The research aimed to evaluate the effect of particle size and adhesives on the quality of biopelet from oil palm trunk. The adhesives used were tapioca and sago. The particle size were pass 10 mesh and retained 20 mesh; pass 20 mesh and retained 40 mesh; pass 40 mesh and retained 60 mesh; and pass 60 mesh. Biopelet was made by meat mincer in home scale and resulted the biopelet with size 2 cm long and diameter 0.4 cm.Â  Biopelet then dry in oven for 24 hour with temperature 600C-700C. The quality of biopelet was evaluate with SNI 8021 : 2014. Result of the research showed that average value of moisture content were 5.27%-6.75% ; average value of ash content 4.69%-8.73%; average of volatile matter content were 72.62%-77.46% ; average value of fixed carbon were 14.02%-21.60%; average value of calor were 3719,67 cal/g-4451,67 cal/g. The quality of biopelet can fulfill the requirement standard of SNI 8021 : 2014, except on ash content. The best result was on particle with size pass 10 mesh and retained 20 mesh with adhesives tapioca. Keyword: Biopelet, bioenergy, sago, tapioca